MENINGKATKAN KETERAMPILAN SPEAKING PADA MATERI TELLING TIME DENGAN MODEL PBL (PROBLEM BASED LEARNING) BERBANTUKAN ONLINE GAME (WORDWALL) DAN WORKSHEET (OFFICE ONLINE) - Rupiah, Sri Nikmatu; Aimah, Siti; Dwiyamtini, Margaretha Rulik (Journal of Lesson Study in Teacher Education, 2024)
This research aims to enhance students’ speaking skill using problem-based learning integrated with online game (word wall) and worksheet (office online). An observation was used to capture how students’ attitude during the teaching and learning process using problem-based learning integrated with word wall and office online. Students’ result of learning, particularly their speaking performance was also used to support the data. The data were then analyzed descriptively to know how students’ learning of speaking in the classroom. The result showed that through problem-based learning integrated with word wall and office online, students learnt comprehensively with others about how to ask for and give a response of telling time. During the teaching and learning process, students performed actively either in their own group or in front of the class.